2016
DOI: 10.1186/s40104-016-0107-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker and pathway analyses of urine metabolomics in dairy cows when corn stover replaces alfalfa hay

Abstract: BackgroundAlfalfa hay and corn stover are different type of forages which can significantly impact a cow’s lactation performance, but the underlying metabolic mechanism has been poorly studied. We used biomarker and pathway analyses to characterize related biomarkers and pathways based on urine metabolomics data from different forage treatments. Urine was collected from 16 multiparous Holstein dairy cows fed alfalfa hay (AH, high-quality forage, n = 8) and corn stover (CS, low-quality forage, n = 8) respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Based on the correlation analysis, Lachnospiraceae_ND3007_group might decrease the concentration of 5-oxoproline and more glutathione was produced in Group H to promote antioxidative capacity. Similarly, previous study also found that the concentration of 4hydroxyphenylacetic acid was decreased when cows were fed with high-quality forage [68]. Microbiota degrade dietary protein to tryptophan, which could be later converted into melatonin [69].…”
Section: Comparison Of the Composition And Differences Of Ruminal Metmentioning
confidence: 57%
“…Based on the correlation analysis, Lachnospiraceae_ND3007_group might decrease the concentration of 5-oxoproline and more glutathione was produced in Group H to promote antioxidative capacity. Similarly, previous study also found that the concentration of 4hydroxyphenylacetic acid was decreased when cows were fed with high-quality forage [68]. Microbiota degrade dietary protein to tryptophan, which could be later converted into melatonin [69].…”
Section: Comparison Of the Composition And Differences Of Ruminal Metmentioning
confidence: 57%
“…e integrated metabolic pathways contain interactive networks, as well as related metabolites, and provide information during chilled ageing. is information extends beyond metabolic relevance and has effects as demonstrated in the pathways and network analyses applied in the metabolomics analyses [30]. e detailed construction of the altered TCA cycle, biosynthesis of alkaloids derived from histidine and purine, and biosynthesis of amino acids with the related metabolites can be used to understand the effects of different storage time points on the altered flavour precursors and provide insights for future mechanistic exploration.…”
Section: Key Metabolic Pathwaysmentioning
confidence: 99%
“…Phenylpyruvic acid is an alpha keto acid that is an intermediate or catabolic byproduct of phenylalanine metabolism (Coban, Demirci, Patterson, & Elias, 2016;Li et al, 2011). When phenylalanine has been absorbed, it may follow one of three pathways: incorporation into body proteins, conversion to tyrosine, or conversion to phenylpyruvic acid (Sun, Wang, Wang, Liu, & Liu, 2016). Similarly, ornithine is one of the products of the action of arginase on arginine (Schneemann & Schoeden, 2007).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%